Winning the Second Battle : Canadian Veterans and the Return to Civilian Life 1915-1930 - Morton, Desmond (Book collections on Project MUSE., 1987)
Desmond Morton and Glenn Wright point out that Canada was a leader among its allies in devising plans for the retraining of disabled soldiers. The story of that defeat, never told until now, reveals a great deal about Canadian government, pressure group, and politics in the interwar period.